Development of Health Educational Game Application â€œWorm Freeâ€ Based on Android - Guspianto, Guspianto; Humaryanto; Yun Nina , Ekawati; Mohamad , Ilhami; Shabira, Diyank (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Background: Strategies for preventing and controlling worms are carried out by increasing PHBS behavior from an early age. Health promotion efforts such as health education for student have been carried out, one of which was through the game method (gamification) which was able to stimulate various senses, attract and be liked by children. In line with the development of communication and information technology, digital-based educational models were very necessary and helpful in improving children's thinking patterns, creativity, and ability to obtain health information. This study aims to develop a digital game application "worm-free" based on Android. Method: This studied conducted Research and Development (R&D) design with five stages namely needs analysis, product design development, validation, revision, limited trial and field test. Result: The validation results of media experts and material experts as well as limited trials concluded that the digital game product was informative, easy to access and use, and interesting so it was very feasible to use and proven to increase PHBS knowledge for Helminthiasis prevention in primary school students. Conclusion: It is recommended that digital game health education "Worm Free" based on Android can be widely utilized by the community, especially elementary school children to increase PHBS knowledge and behavior to prevent worms from early age.